Importancia del CRM en el sector de servicios renting vehicular ante la actual crisis COVID-19 en el Perú - Huaman Gavino, Hector Arturo (2021)
In this research work, a study will be carried out on the level of impact that good customer relationship management has for service companies in the vehicle renting sector in the face of the current COVID-19 crisis in Peru. The main conclusion is the high degree of importance of a good CRM in the vehicle renting sector, much more in times of crisis, where customer loyalty is at stake.